Perancangan Sistem Pengolahan Hasil Assessment Value dan Analisis Persepsi Kandidat Terhadap Manajemen Kinerja di PT. X - Ivana Vivian Chandra (Jurnal Titra, 2022)
Designing processing system on value assessment is needed to process data that related to the suitability of the candidate's value with the company. Candidates are interns who are doing the internship program in the company. The purpose of this research is to make the evaluation and analyzation about candidate’s value easier for user from Human Capital Department, specifically Talent Acquisition and helps recruitment process running more effectively because the results of value assessment are one of the considerations to decide whether the candidate is eligible to take part on the next stage. The designed formula will generate the data needed by the user automatically according to the responses obtained from the google form, and will be updated in real time. One of the situations experienced by candidates regarding to their value is directly related to the performance management in the company, especially performance management implemented by their direct supervisor. Therefore, this research wanted to know whether the performance management implemented in the company was in line with the expectations of the candidates. Then it will be analyzed which aspects of performance management need to be maintained or improved in order to support the company's sustainability and success.